Integrative transcriptomic analysis in human and mouse model of anaphylaxis identifies gene signatures associated with cell movement, migration and neuroinflammatory signalling - Rijavec, Matija; Maver, Aleš; Turner, Paul J.; Hočevar, Keli; Košnik, Mitja; Yamani, Amnah; Hogan, Simon P.; Custovic, Adnan; Peterlin, Borut; Korošec, Peter (Frontiers in Immunology, 2022)
Background: Anaphylaxis is an acute life-threatening allergic reaction and a concern at a global level; therefore, further progress in understanding the underlying mechanisms and more effective strategies for diagnosis, prevention and management are needed. Objective: We sought to identify the global architecture of blood transcriptomic features of anaphylaxis by integrating expression data from the human and murine models of anaphylaxis. Methods: Bulk RNA-sequencings of peripheral whole blood were performed in: i) 14 emergency department (ED) patients with acute anaphylaxis, predominantly to Hymenoptera venom, ii) 11 patients with peanut allergy undergoing double-blind, placebo-controlled food challenge (DBPCFC) to peanut, iii) murine model of IgE-mediated anaphylaxis. Integrative characterisation of differential gene expression, immune cell-type-specific gene expression profiles, and functional and pathway analysis was undertaken. Results: 1023 genes were commonly and significantly dysregulated during anaphylaxis in ED and DBPCFC patients; of those genes, 29 were also dysregulated in the mouse model. Cell-type-specific gene expression profiles showed a rapid downregulation of blood basophil and upregulation of neutrophil signature in ED and DBPCFC patients and the mouse model, but no consistent and/or significant differences were found for other blood cells. Functional and pathway analysis demonstrated that human and mouse blood transcriptomic signatures of anaphylaxis follow trajectories of upregulation of cell movement, migration and neuroinflammatory signalling, and downregulation of lipid activating nuclear receptors signalling. Conclusion: Our study highlights the matched and extensive blood transcriptomic changes and suggests the involvement of discrete cellular components and upregulation of migration and neuroinflammatory pathways during anaphylaxis.